Attention is prioritised for proximate and approaching fearful faces. (January 2021) - Martin, Aimee; Becker, Stefanie I.; Pegna, Alan J.
Abstract: Attention is an important function that allows us to selectively enhance the processing of relevant stimuli in our environment. Fittingly, a number of studies have revealed that potentially threatening/fearful stimuli capture attention more efficiently. Interestingly, in separate fMRI studies, threatening stimuli situated close to viewers were found to enhance brain activity in fear-relevant areas more than stimuli that were further away. Despite these observations, few studies have examined the effect of personal distance on attentional capture by emotional stimuli. Using electroencephalography (EEG), the current investigation addressed this question by investigating attentional capture of emotional faces that were either looming/receding, or were situated at different distances from the viewer. In Experiment 1, participants carried out an incidental task while looming or receding fearful and neutral faces were presented bilaterally. A significant lateralised N170 and N2pc were found for a looming upright fearful face, however no significant components were found for a looming upright neutral face or inverted fearful and neutral faces. In Experiment 2, participants made gender judgements of emotional faces that appeared on a screen situated within or beyond peripersonal space (respectively 50 cm or 120 cm). Although response times did not differ, significantly more errors were made when faces appeared in near as opposed to far space. Importantly, ERPs revealed a significant N2pc for fearful faces presented in peripersonal distance, compared to the far distance. Our findings show that personal distance markedly affects neural responses to emotional stimuli, with increased attention towards fearful upright faces that appear in close distance.